Body Mass Index, Overweight, and Obesity in Swedish Women Born Post‐term. Issue 4 (25th March 2016) - Derraik, José G. B.; Lundgren, Maria; Cutfield, Wayne S.; Ahlsson, Fredrik
Abstract: Background: There is increasing evidence that post‐term birth (≥42 weeks of gestation) is associated with adverse long‐term outcomes. We assessed whether women born post‐term displayed increased risk of overweight and obesity in adulthood. Methods: Data were collected at first antenatal visit (~10–12 weeks of gestation) on singleton Swedish women aged ≥18 years in 1991–2009 (mean age 26.1 years), who were born post‐term ( n = 27 153) or at term (37–41 weeks of gestation; n = 184 245). Study outcomes were evaluated for continuous associations with gestational age. Stratified analyses were carried out comparing women born post‐term or at term. Analyses were also run with a 2‐week buffer between groups to account for possible errors in gestational age estimation, comparing women born very post‐term (≥43 weeks of gestation; n = 5761) to those born within a narrower term window (38–40 weeks of gestation; n = 130 110). Results: Increasing gestational age was associated with greater adult weight and body mass index (BMI). Stratified analyses showed that women born post‐term were 0.5 kg heavier and had BMI 0.2 kg/m 2 greater than those born at term. Differences were more marked between women born very post‐term (≥43 weeks) vs. a narrower term group (38–40 weeks): 1.0 kg and 0.3 kg/m 2 . The adjusted relative risks of overweight/obesity and obesity in women born very post‐term were 1.13 and 1.12 times higher, respectively, than in those born at term. Conclusions: Post‐term birth is associated with greater BMI and increased risk of overweight and obesity in adulthood, particularly among women born ≥43 weeks of gestation.